2012
DOI: 10.1111/j.1752-699x.2012.00311.x
|View full text |Cite
|
Sign up to set email alerts
|

Training on a new, portable, simple simulator transfers to performance of complex bronchoscopy procedures

Abstract: The effect of a brief, self-directed training session using a portable, simple simulator was substantial and transferred to performance of more complex skills.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
29
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 19 publications
(31 citation statements)
references
References 29 publications
0
29
0
Order By: Relevance
“…has a steep learning curve) there will be a considerable ceiling effect allowing trainees to pass the test after a brief training session. A study on flexible bronchoscopy simulation showed no differences between novices that had tried the simulator 5 times and experts [23], and in another study, 8 out of 10 medical students passed a simulator test after 1-3 h of training [24]. EBUS-TBNA is a difficult procedure to master and the fact that approximately 2 h of training did not allow the trainees to reach expert performance indicates that the VR simulator mimics the difficulties of real-life patients, and that the QS is an appropriate measure of competence.…”
Section: Discussionmentioning
confidence: 99%
“…has a steep learning curve) there will be a considerable ceiling effect allowing trainees to pass the test after a brief training session. A study on flexible bronchoscopy simulation showed no differences between novices that had tried the simulator 5 times and experts [23], and in another study, 8 out of 10 medical students passed a simulator test after 1-3 h of training [24]. EBUS-TBNA is a difficult procedure to master and the fact that approximately 2 h of training did not allow the trainees to reach expert performance indicates that the VR simulator mimics the difficulties of real-life patients, and that the QS is an appropriate measure of competence.…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, it does not make sense to know the anatomy if you are not able to take biopsies. Krogh et al [16] and Konge et al [17] used the same assessment method, which ensures a comprehensive rating not only because of the equal emphasis on both anatomy and biopsy taking, but also because of its ability to discriminate between varying degrees of experience.…”
Section: Discussionmentioning
confidence: 99%
“…Of all the publications on flexible bronchoscopy, only a few included biopsies as an essential part of the operator assessment [16][17][18] . Two studies used the BSTAT during which the operator might be asked to perform a biopsy as 1 of a few standard tasks [20,24] .…”
Section: Assessmentmentioning
confidence: 99%
See 1 more Smart Citation
“…Bronchoscopes and bronchoscopic procedures are changing as manufacturers move into GPS-like navigational devices, 3D stereoscopic instruments with enhanced optics, and multimodality devices that incorporate optical and acoustic and nano technology. Concurrently, educational opportunities are increasing because of new educational techniques, easily transportable and less expense computer-based simulators, and wider dissemination of affordable inanimate models [28,29].…”
Section: New Developments In Education Simulation and Computer Gamingmentioning
confidence: 99%